Pathogen-derived biomarkers for active tuberculosis diagnosis - Tucci, Paula; González-Sapienza, Gualberto; Marin, Monica (Frontiers in Microbiology, 2014)
Tuberculosis (TB) is an infectious disease caused by members of Mycobacterium tuberculosis complex. Despite the availability of effective treatments, tuberculosis remains a major public health concern in most low and middle-income countries, representing worldwide the second leading cause of death from an infectious disease. Inadequate case detection and failures to classify the disease status hamper proper tuberculosis control. The limitations of the conventional diagnostic methods have encouraged much research activities in this field, but there is still an urgent need for an accurate point of care test for active tuberculosis diagnosis. A rapid, precise, and inexpensive tuberculosis diagnostic test would allow an earlier implementation of an appropriate treatment and the reduction of disease transmission. Pathogen-derived molecules present in clinical specimens of affected patients are being validated for that purpose. This short review aims to summarize the available data regarding biomarkers derived from M. tuberculosis, and their current usage in active tuberculosis diagnosis.